Challenges in the morphological diagnostics of infectious lung diseases among HIV-infected patients: a case-series study - I. V. Liskina; O. D. Nikolaieva; O. O. Melnyk; L. M. Zahaba (Zaporožskij Medicinskij Žurnal)
HIV-infection is a long-term infectious disease, characterized by deterioration of the immune system and it is often complicated by the development of opportunistic diseases, mainly of infectious origin. HIV-associated infections become generalized in the late stages of the disease and often may combine, that makes challenges in the diagnosis of these diseases. Differential morphological diagnosis of HIV-associated lung infections is quite complex. Most frequently, there is the need to differentiate between tuberculosis, bacterial or septic pneumonia, cytomegalovirus lung lesions, and deep mycoses.